Ideological Polarization in Online News Comment Sections: A Critical Discourse Analysis of Digital Language - Reva Angelina; Ester Monica Bu’ulolo; Fadillah Fauziah Putri; Rebecha Silalahi (Student Research Journal, 2026)
This study examines ideological polarization in online news comment sections through a Critical Discourse Analysis (CDA) approach. In recent years, digital platforms have increasingly become sites of discursive contestation where ideological divisions are intensified rather than mitigated. Using a qualitative interpretive design, this study analyzes approximately 300 user comments on political news articles collected through purposive sampling. The analysis applies van Dijk’s socio-cognitive model, focusing on textual structures, social cognition, and social context. The findings reveal three dominant patterns: (1) the construction of “us versus them” dichotomies through evaluative and exclusionary language, (2) the use of emotional and stigmatizing discourse as a mechanism of ideological legitimation, and (3) the recursive reproduction of polarization through interactive comment chains. Drawing on recent studies in digital communication and polarization, the findings demonstrate that online language operates as a form of symbolic power that reinforces group boundaries and social fragmentation. This study contributes to contemporary digital discourse research by emphasizing the importance of critical digital literacy and micro-level discursive analysis in understanding ideological polarization.